Bridging the Divide: Analyzing the Gap Between Engineering Education and Industry Institute Interaction in Kerala - Mahendra, K. S; Kinslin, D; Janardhanan, K. A; Deekshith, D (Indian Journal of Information Sources and Services, 2025)
This thesis is mainly about interactions between engineering educational institutions and industrial institutions in Kerala. In India itself, Kerala had a high rating in terms of education, but students in Kerala, especially students in engineering education, faced many difficulties in getting the jobs they wanted. There was a gap between educational institutions and industrial institutions. The main reason for that gap was the misalignment of curricula, and teachers had a lot to say about its importance. These reasons often resulted in insufficient involvement from industry in educational institutions. Even if they were brilliant students, there were not enough opportunities for industries to take notice of them. But this problem can be solved to some extent through curriculum reform to fill this gap, faculty development, collaboration with industry academia, and support from the government. This thesis addresses the bridging or potential bridging of the gap between industry and educational institutions. In recent times career was not given much importance other than to make the students smart as taught by the educational institutions but according to the changed situation students after graduation in one of the special professional courses like engineering give great importance to the job. They are looking for their job prospects after their studies or along with their studies because the importance of which institutes are providing it i.e. which educational institutes are providing placements is now becomes more important and that is what this paper is about discussing.